Scotland׳s hydropower: Current capacity, future potential and the possible impacts of climate change. (December 2015) - Sample, James E.; Duncan, Niall; Ferguson, Michael; Cooksley, Susan
Abstract: To promote the transition towards a low carbon economy, the Scottish Government has adopted ambitious energy-related targets, including generating all electricity from renewable sources by 2020. To achieve this, continued investment will be required across a range of sustainable technologies. Hydropower has a long history in Scotland and the present-day operational capacity of ~1.5 GW already makes a substantial contribution to the national energy budget. In addition, there remains potential for ~500 MW of further development, mostly in the form of small to medium size run-of-river schemes. Climate change is expected to lead to an intensification of the global hydrological cycle, leading to changes in both the magnitude and seasonality of river flows. There may also be indirect effects on water flows, such as changing land use, enhanced evapotranspiration rates and an increased demand for irrigation, all of which could affect the water available for energy generation. In this paper we describe Scotland׳s currently installed hydropower capacity and present a review of the scope for future development. We also review the potential impacts of climate change, highlighting possible adaptation measures as well as key factors likely to determine financial viability over the coming decades. We present a summary of the present state of knowledge regarding the resilience of Scotland׳s hydropower resource to a changing climate, and identify key areas where further research is required.